Mineral composition controls the stabilization of microbially derived carbon and nitrogen in soils: Insights from an isotope tracing model - Wang, Xu; Wang, Chao; Fan, Xianlei; Sun, Lifei; Sang, Changpeng; Wang, Xugao; Jiang, Ping; Fang, Yunting; Bai, Edith (Global change biology, 2024)
Evidence is emerging that microbial products and residues (necromass) contribute greatly to stable soil organic matter (SOM), which calls for the necessity of separating the microbial necromass from other SOM pools in models. However, the understanding on how microbial necromass stabilizes in soil, especially the mineral protection mechanisms, is still lacking. Here, we incubated 13C‐ and 15N‐labelled microbial necromass in a series of artificial soils varying in clay minerals and metal oxides. We found the mineralization, adsorption and desorption rate constants of necromass nitrogen were higher than those of necromass carbon. The accumulation rates of necromass carbon and nitrogen in mineral‐associated SOM were positively correlated with the specific surface area of clay minerals. Our results provide direct evidence for the protection role of mineral in microbial necromass stabilization and provide a platform for simulating microbial necromass separately in SOM models. Schematic diagram of microbially derived carbon and nitrogen cycling among different pools in soil.